Advanced Biomedical Engineering - Gargiulo, Gaetano D.; McEwan, Alistair (IntechOpen, 2011)
This book presents a collection of recent and extended academic works in selected topics of biomedical signal processing, bio-imaging and biomedical ethics and legislation. This wide range of topics provide a valuable update to researchers in the multidisciplinary area of biomedical engineering and an interesting introduction for engineers new to the area. The techniques covered include modelling, experimentation and discussion with the application areas ranging from acoustics to oncology, health education and cardiovascular disease.